Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. The role of the enrichment activities in "Loughati Alkhalida" course in the development of Oral expression skills from the point of view of the female teachers Fatema Obeid Alharbi, Nabilah Taher Ali Al-Tunisi 2. The reality of using smart devices to develop the linguistic abilities of older first-year students Researcher / Mona Mabrouk Moawad Al-Juhani, Dr. Mashael Saleh Al-Dosari 3. The role of social networks in reducing educational loss among primary level students from the point of view of Al Sera basic school teachers in the South Hebron Directorate of Education. (Qualitative study) Sahar Rjoub, A. Dr. Ibrahim Arman 4. The Effect of Teaching-Based Competencies on The Seventh Graders’ Achievement and Their attitudes towards Learning Mathematics in Nablus Governorate Saja Akram Fares 5. Integrated Approach in Teaching Language between Theory and Practice Dr.Mohammad Fawzy Bani-Yaseen, Prof. Mohammad Akram Alzu’bi, Dr. Ali Mahmoud Al Tawalbeh